2022
DOI: 10.3390/microorganisms10102081
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Microbiomes of Leopard Sharks (Triakis semifasciata) Are Consistent across Captive and Wild Environments

Abstract: Characterizations of shark-microbe systems in wild environments have outlined patterns of species-specific microbiomes; however, whether captivity affects these trends has yet to be determined. We used high-throughput shotgun sequencing to assess the epidermal microbiome belonging to leopard sharks (Triakis semifasciata) in captive (Birch Aquarium, La Jolla California born and held permanently in captivity), semi-captive (held in captivity for <1 year in duration and scheduled for release; Scripps Institute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 82 publications
2
4
0
Order By: Relevance
“…The abundant core was identified by assemblying the single reads into Metagenome Assembled Genomes (MAGs). The number of MAGs characterized in our study (35 high quality) was similar to two other studies focused on shark microbiomes, one which found 54 high/medium quality MAGs from the skin surface of leopard sharks ( Triakis semifasciata ) 28 and another that found 27 MAGs from feacal samples of two shark species 29 . These abundant core microbes may be supporting microbiome architectural patterns by providing metabolic processes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The abundant core was identified by assemblying the single reads into Metagenome Assembled Genomes (MAGs). The number of MAGs characterized in our study (35 high quality) was similar to two other studies focused on shark microbiomes, one which found 54 high/medium quality MAGs from the skin surface of leopard sharks ( Triakis semifasciata ) 28 and another that found 27 MAGs from feacal samples of two shark species 29 . These abundant core microbes may be supporting microbiome architectural patterns by providing metabolic processes.…”
Section: Discussionsupporting
confidence: 85%
“…Interestingly, microbes of these taxonomic groups are commonly associated with fish mucus microbiomes 30 and may indicate a similar role in the epidermal microbiome. Flavobacteracaea MAGs were found from the epidermal microbiome of the leopard shark ( T. semifasciata) 28 , suggesting this microbial family my be a symbiont of marine fishes (bony and cartilaginous). Gene pathways in Ecogroup 1 support this groups role as skin microbiome symbionts that utilize mucus.…”
Section: Discussionmentioning
confidence: 99%
“…Even though each host harbored a species-specific microbiome, we did observe some common features. Most notably, the Pseudoalteromonadaceae family was dominant across all shark hosts, consistent with microbiome surveys of T. semifasciata 16 . This family of bacteria is well-known for its crucial roles in biofilm formation and the deterrence of potential microbial predator colonization 43,44 .…”
Section: Discussionsupporting
confidence: 79%
“…The epidermal microbiomes of sharks, which have densely packed denticles, are highly shared across individuals of the same species, while the epidermal microbiomes of stingray, which have sparse dermal denticles and thick mucus, are more variable, suggesting the interaction of dermal denticles and microbiome characteristics 15,16 . Thus, while microbes pervasively associated with the epidermis of fishes throughout the host's evolutionary history, describing the specific microbial species present on the skin of marine vertebrates and the host factors influencing microbiome recruitment and retainment is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation